2014
DOI: 10.1155/2014/535640
|View full text |Cite
|
Sign up to set email alerts
|

Sintering Behavior of CNT Reinforced Al6061 and Al2124 Nanocomposites

Abstract: Ball milling and spark plasma sintering were successfully used to produce carbon nanotube reinforced Al6061 and Al2124 nanocomposites which have potential applications in the fields of aerospace, automotive, electronics, and high precision instrumentation. Al2124 and Al6061 nanocomposite powders containing 0.5 to 2 wt.% CNTs prepared through sonication and wet ball milling were spark plasma sintered at 400, 450, and 500°C for 20 minutes under a pressure of 35 MPa. CNTs were better dispersed, and less agglomera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…3d) was responsible for its better relative density in comparison to the composites with 2 and 3 wt % MWCNTGr (Figs. 3e and f) respectively.These observations are in agreement with the reports of a similar study by Saheb et al [49] on the reinforcement of Al alloys with CNTs.The higher relative density in the composite with 1 wt % MWCNTGrwas most probably due to the relative homogeneous dispersion of the MWCNTGr within the metal matrix and not due to the supposed minor detrimental effect of a lower weight fraction of MWCNTGr. This position was premised on a previous study by Wang et al [45] wherein Between 850 and 1000 °C,the relative densities improved by 1.2, 0.5 and 1.7 % with 1, 2 and 3 wt % MWCNTGr respectively in the sintered composites.…”
Section: Influence Of Sintering Temperature On the Densificationof Mwsupporting
confidence: 94%
“…3d) was responsible for its better relative density in comparison to the composites with 2 and 3 wt % MWCNTGr (Figs. 3e and f) respectively.These observations are in agreement with the reports of a similar study by Saheb et al [49] on the reinforcement of Al alloys with CNTs.The higher relative density in the composite with 1 wt % MWCNTGrwas most probably due to the relative homogeneous dispersion of the MWCNTGr within the metal matrix and not due to the supposed minor detrimental effect of a lower weight fraction of MWCNTGr. This position was premised on a previous study by Wang et al [45] wherein Between 850 and 1000 °C,the relative densities improved by 1.2, 0.5 and 1.7 % with 1, 2 and 3 wt % MWCNTGr respectively in the sintered composites.…”
Section: Influence Of Sintering Temperature On the Densificationof Mwsupporting
confidence: 94%
“…However, during short milling, the addition of higher contents of CNT can have an adverse effect on the densification and homogeneity of the resulting alloys. It was reported elsewhere [33] that the porosity level is increased with increasing the CNT content since more CNT's can lead to forming agglomerates which cause less uniform and homogeneous alloys. Therefore, the results presented later in this work will be limited to CNT content of 0.5 wt% as it shows promising results in terms of homogeneity and distribution of CNT's into the alloy matrix.…”
Section: Sem Micrographs Of As-received and Milled Powdersmentioning
confidence: 89%
“…The nanocomposites had Vickers hardness twice as high as that of the microcomposites. Saheb and coworkers [62] successfully produced carbon nanotube-reinforced Al6061 and Al2124 nanocomposites using ball milling and spark plasma sintering. They reported that CNTs were better dispersed, less agglomerated, and had good adhesion to the matrix in composites containing 1 wt.% CNTs.…”
Section: Spark-plasma-sintered Metal Matrix Nanocompositesmentioning
confidence: 99%